Experimental passive eavesdropping of Digital Enhanced Cordless Telecommunication voice communications through low‐cost software‐defined radios. Issue 3 (17th March 2014) - Sanchez, Ignacio; Baldini, Gianmarco; Shaw, David; Giuliani, Raimondo
Abstract The flexibility of software‐defined radio (SDR) technology has been proposed to support various applications from the dynamic usage of the radio frequency spectrum to the implementation of radio access technologies in the commercial and military domain. A new generation of low‐cost SDR devices has emerged in the last few years, opening new possibilities to implement inexpensive security attacks against radio protocols and systems. Digital Enhanced Cordless Telecommunication (DECT) is a European Telecommunications Standards Institute standard for short‐range cordless communications with a worldwide installed base. In this paper, we survey the state of art for the application of low‐cost SDRs to the security domain, and we describe a complete implementation of a passive eavesdropping attack against DECT digital voice communication, where the DECT communication is not encrypted. The framework, which implements the attack, has been deployed on two different types of low‐cost SDR platforms to show the flexibility and extendibility of the implementation. The performance of the framework has been evaluated on the basis of different parameters and different approaches, and the experimental results are presented in the paper. The framework has demonstrated its effectiveness to implement an eavesdropping attack against DECT even at great distances with low‐cost equipment.Copyright © 2014 John Wiley & Sons, Ltd.